CROSS-CULTURAL STUDY OF RUSSIAN AND CHINESE STUDENTS AS DECISION-MAKERS - Andreev, Anatoliy; Shafazhinskaya, Natalya; Aralova, Elena; Goltseva, Oksana; Pisarevskiy, Konstantin (Revista Inclusiones, 2019)
The article aims to study the specifics of financial decisions made by Russian and Chinese students. The article determines six potential strategies for making financial decisions: "maximum selfishness", "moderate selfishness", "egalitarian strategy", "selflessness without personal losses", "maximum selflessness" and "inconsistent strategy". The authors of the article have demonstrated that the most common strategy among all students was the "egalitarian strategy". The strategy of "maximum selfishness" was less common and the strategy of "selflessness without personal losses" was the least popular. The authors have also proved that the Russian students tended to use the strategy of "maximum selfishness", while the Chinese students preferred the "egalitarian strategy". On the one hand, the authors have studied interconnections of financial decision-making strategies. On the other hand, they have determined the level of national identity, envy and collectivismindividualism. It has been established that financial decision-making strategies were statistically significant and correlated only with the level of national identity. Moreover, these relations have their own specific features for each national group under study.